Analisa Pengaruh Experiential Marketing, Emotional Marketing Dan Psikologi Konsumen Terhadap Loyalitas Pelanggan Pada Toko Rositha Putra Bvr Bengkulu - Refi Refi (STIE AMKOP, 2023)
This study aims to determine experiential marketing, emotional marketing and consumer psychology to customer loyalty at the Rositha Putra Bengkulu Skincare Store. The population in this study are all consumers who shop at Rositha Putra BVR Bengkulu Stores. The sample of this research is 100 consumers who shop at Toko Rositha Putra BVR Bengkulu. In this study the sampling technique used was accidental sampling technique. The method of analysis of this research is a quantitative method using multiple linear regression analysis tools, multiple correlation, determination, F test and t test which are processed using IBM SPSS 20 software. From the results of the study it can be concluded that experiential marketing, emotional marketing and consumer psychology affect customer loyalty. Experiential marketing, emotional marketing and consumer psychology to customer loyalty at Toko Rositha Putra BVR Bengkulu. keywords: Experiential Marketing, Emotional Marketing, Consumer Psychology And Customer Loyalty